105k views
1 vote
Which equation is the inverse of (x minus 4) squared minus two-thirds = 6y minus 12?

y = one-sixth x squared minus four-thirds x + StartFraction 43 Over 9 EndFraction
y = 4 plus-or-minus StartRoot 6 x minus StartFraction 34 Over 3 EndFraction EndRoot
y = negative 4 plus-or-minus StartRoot 6 x minus StartFraction 34 Over 3 EndFraction EndRoot
negative (x minus 4) squared minus two-thirds = negative 6 y + 12

if u wanna talk

1 Answer

1 vote

(x minus 4) squared minus two-thirds = 6y minus 12?

y = one-sixth x squared minus four-thirds x + StartFraction 43 Over 9 EndFraction

y = 4 plus-or-minus StartRoot 6 x minus StartFraction 34 Over 3 EndFraction EndRoot

y = negative 4 plus-or-minus StartRoot 6 x minus StartFraction 34 Over 3 EndFraction EndRoot

negative (x minus 4) squared minus two-thirds = negative 6 y + 12

I don't even understand ur question...... ~~~ sure let's talk :))

User Derek Story
by
4.6k points